CLINICAL AND HEMATOLOGICAL INDICATIONS OF FISH PROTEIN METABOLISM DISORDERS (Proceedings of International Conference on Educational Discoveries and Humanities, 2023)
This in the article fishes between occurring protein exchange in disorders in fish show to be clinical characters appetite loss , coxixia development growth and from development medium stay and your blood biochemical indicators protein exchange in disorders changes about data given .